Multimodal insights: enhancing cultural promotion through analysis of Saudi Arabian audiovisual productions - Sara AlShubaily (Humanities & Social Sciences Communications)
Abstract This research explores the application of Dicerto’s (2018) multimodal pragmatic model in analyzing Arabic audiovisual productions for translation purposes, focusing on enhancing cultural promotion. Employing a qualitative descriptive analysis approach, the study examines samples from Saudi productions that promote tourism, mainly focusing on Saudi coffee and its cultural traditions to enlighten foreign visitors about Saudi culture. The analysis reveals that Dicerto’s model provides a clear framework for achieving semantic fidelity in translation, ensuring that the translated text closely resembles its original in interpretative richness. Central to this framework is the principle of optimal relevance, wherein the sender intends the message to be maximally pertinent to the audience, thereby justifying the recipient’s cognitive effort in processing it and facilitating access to the sender’s intentions. This research sheds light on the effectiveness of applying multimodal analysis models in cultural promotion efforts through audiovisual productions, particularly in Saudi Arabian tourism promotion.